Analysis of Kazakhstan’s regional technoparks activity - Satpayeva , Z.T. (BUKETOV BUSINESS REVIEW, 2019)
The article is devoted to the study of Kazakhstan’s regional technoparks activities. The main research method was the economic and statistical analysis. The information base was the analytical reports of JSC «National Agency for Technological Development» and data from the websites of regional technoparks. The limitation of the research was the lack of public reports on its activities in the majority of regional technoparks. The analysis revealed that since 2004 in Kazakhstan 10 regional technoparks mainly providing the medium-tech sector of the economy were established with the participation of the state budget funds. However, today there are only 5 technology parks, which is largely due to the low efficiency of their activities. In recent years, activity has been done on transferring regional technoparks to a competitive environment, which requires a revision of «technopark» concept in The Entrepreneurial Code of the Republic of Kazakhstan and the development of regulatory documents defining its activities.